PENINGKATAN EFISIENSI PRODUKSI MINUMAN SARI STROBERI (Fragariax annasa D) DAN TAMARILLO (Chypomandra betacea) - Erryana Martati (Journal of Innovation and Applied Technology, 2016)
Strawberry and tamarillo are antioxidant rich fruits that suitable for health functional drinks.  Tamarillo is rich in anthocyanin and carotenoids, meanwhile straxberry has high anthocianin content.  Two small medium entreprises (SMEs) in Batu City that produces strawberry and tamarillo drinks are SME Natural and SME Ridha Nabilla, separately. Both products have high marketing prospect because Batu in one of tour destinations.  However, both SMEs have difficulty to grow their business due to small capacity and inefficiency of both antioxidant rich drinks. This program is aimed to solve the problems in low capacity and inefficiency of strawberry drink production, i.e. extraction, filtration, and packaging, as well as the problem in production of strabwerry jam from strawberry cake. Meanwhile the problem of tamarillo drink production is limited capacity of extraction, filtration, and packaging. Method of this program was technology transfer of mechanical processing by using industrial boiling stainles pan, acceleration of sedimentation by using sentrifuge, increasing packaging capacity and efficiency by semi automatic cup sealer, and increasing strawberry cake crushing by using industrial blender.   Also, the implementation of Good Manufacturing Practices was conducted step by step through accompaniment. The results showed that both antioxidant rich drink SMEs can increase their production capacity and efficiency in extraction, filtration, and packaging.  Capacity of extraction increase 4-5 times compared to capacity before the program.  Filtration efficiency increases by reduction time of filtration from 1 day to 15 min.  Semi automatic cup sealer can increase packaging capacity from 300 to 1500 cups/day.  Strawberry cake crushing also increases by using industrial blender with capacity 30 kg/batch.  Both SMEs gradually implement the GMP to produce safe and qualified products.